A trajectory-based classification of ERA-Interim ice clouds in the region of the North Atlantic storm track - Wernli, Heini; id_orcid:0 000-0001-9674-4837; Boettcher, Maxi; Joos, Hanna; Miltenberger, Annette K.; Spichtinger, Peter (Geophysical Research Letters, 2016)
ISSN:0094-8276 ISSN:1944-8007